The Market Pricing of Special Items that are Included in versus Excluded from Street Earnings* - Hsu, Charles; Kross, William (Contemporary Accounting Research, 2011)
We re-investigate the market pricing of special items, with particular emphasis on how managers " frame " these non-operating earnings components via their inclusion or exclusion from " street " earnings, the earnings numbers that firms disclose in their press releases and that analysts track and forecast. When managers include the special items in " street earnings (i.e., " street " = GAAP), the market overprices them, believing the special items to be more persistent than they actually are. As a result, there is a negative relationship between the special items and future stock returns in the following year. However, when managers exclude special items from " street " earnings (i.e., " street " not equal GAAP), the market recognizes their transitory characteristic and the relationship between special items and returns is insignificant in the following year. We also demonstrate that the decision to include (exclude) special items with (from) " street " earnings is associated with whether inclusion or exclusion of special items a) increases earnings numbers, b) smoothes the earnings series, or c) helps managers to meet earnings benchmarks. These results suggest that the decision to include or exclude special items from " street " earnings is associated with managerial incentives to manage earnings numbers rather than signal the persistence of special items.